Alleviatory Role of Panax Notoginseng Saponins in Modulating Inflammation and Pulmonary Vascular Remodeling in Chronic Obstructive Pulmonary Disease: mechanisms and Implications - Yanan Hu; Qiuyang Fan; Bo Qiao; Ou Xu; Bijun Lv; Niping Han; Xiaomei Zhang (COPD)
COPD is an inflammatory lung disease that limits airflow and remodels the pulmonary vascular system. This study delves into the therapeutic potential and mechanistic underpinnings of Panax notoginseng Saponins (PNS) in alleviating inflammation and pulmonary vascular remodeling in a COPD rat model. Symmap and ETCM databases provided Panax notoginseng-related target genes, and the CTD and DisGeNET databases provided COPD-related genes. Intersection genes were subjected to protein-protein interaction analysis and pathway enrichment to identify downstream pathways. A COPD rat model was established, with groups receiving varying doses of PNS and a Roxithromycin control. The pathological changes in lung tissue and vasculature were examined using histological staining, while molecular alterations were explored through ELISA, RT-PCR, and Western blot. Network pharmacology research suggested PNS may affect the TLR4/NF-κB pathway linked to COPD development. The study revealed that, in contrast to the control group, the COPD model exhibited a significant increase in inflammatory markers and pathway components such as TLR4, NF-κB, HIF-1α, VEGF, ICAM-1, SELE mRNA, and serum TNF-α, IL-8, and IL-1β. Treatment with PNS notably decreased these markers and mitigated inflammation around the bronchi and vessels. Taken together, the study underscores the potential of PNS in reducing lung inflammation and vascular remodeling in COPD rats, primarily via modulation of the TLR4/NF-κB/HIF-1α/VEGF pathway. This research offers valuable insights for developing new therapeutic strategies for managing and preventing COPD.